Developing the fun and educative module in plant morphology and anatomy learning for tenth graders - Suciyati, Alfi; Adian, Tabita (University of Muhammadiyah Malang, 2018)
This research aims to examine the eligibility of and responses from expert media, expert material, practitioners and studentsâ on the âFun and Educativeâ biology module. The module was developed in a fun and educative way presenting various educative games. The research development model is using ADDIE model that consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The data collection technique employed examination of learning media experts, material experts, practitioners (biology teachers), and students. The data of research was analyzed in descriptive-qualitative and descriptive-qualitative ways. The results of evaluation on the moduleâs eligibility convey that the learning media expert gave 87.69% with the category of âhighly eligibleâ, the material expert gave 86.00% with the category of âhighly eligible, and the practitioners gave 83.68% with the category of âeligible. The students responses to questionnaires given related to the developed module gave 90.00% with the category of âhighly interesting. Based on the results of examination by the media expert, material expert, practitioners, and students, conclude that the module has fulfilled the criteria of good and eligible learning material and can be used for studying biology.